SEBARAN KERUANGAN SEKTOR EKONOMI DAN KOMODITAS UNGGULAN TAHUN 2005-2010 DI KOTA BANJAR - , DIYAS KURNIAWAN, Dr. M.R. Djarot Sadharto W., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Banjar, one of the unfoldment city from District Ciamis, is located in the southeast of West Java Province. As a new region, Banjar need to fasilitate themselves to develop the region, included in economic sector. Physical, social, and economical potential can be used as the basis for developing the region. The Aims of this reaserch are to analyze and to classify economic growth in Banjar City between 2005-2010, to analyze superior sector (basic sector) in Banjar between 2005-2010, to analyze superior commodities and their spatial distribution in Banjar and to arrange the direction of regional development policies related to superior commodities. The research methods involves secondary data analysis (quantitative) by using: 1) klassen typology analysis to classify economic sector in Banjar, 2) LQ (location quotientt) analysis to determine basis and nonbasis sector in Banjar (the regionsâs economy), 3) the combination of specialization coefficient and location quotientt to acquiring the main commodities and superior commodities, 4) SWOT analysis used to determine policies taken in superior commodities development and regional development. The result of this research: 1) Show services sector is the only sector that developed and grew rapidly in Banjar